2015
DOI: 10.1080/09712119.2015.1031765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzoic acid, essential oils andEnterococcus faeciumSF68 on growth performance, nutrient digestibility, blood profiles, faecal microbiota and faecal noxious gas emission in weanling pigs

Abstract: A total of 150 weanling pigs (body weight of 8.86 ± 0.93 kg) were used in a 42-day trial to evaluate the efficacy of benzoic acid (BA), essential oils (EO) and Enterococcus faecium SF68. Pigs were randomly distributed into five treatments (six replicates and five pigs per pen): CON, control diet; B5E, CON + 0.5% BA + 0.01% EO; B5SF, CON + 0.5% BA + 7 × 10 8 CFU/kg E. faecium; B3E, CON + 0.3% BA + 0.01% EO; B3SF, CON + 0.3% BA + 7 × 10 8 CFU/ kg E. faecium. During d 8-21 and overall, pigs fed B5E diets showed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…In a similar study, with weanling piglets, Mohana Devi and observed that the ATTD of DM and N were increased by supplementation with a combination of MCFAs (caproic acid, caprylic acid, capric acid, and lauric acid) and E. faecium DSM 7134 compared with control diet or diets supplemented with MCFAs or E. faecium DSM 7134 alone. Zhang et al (2016) also demonstrated that a combination of benzoic acid and E. faecium SF68 had positive effect on ATTD of N. In the present study, the increased ATTD of DM and N may be a possible reason for the improvement in growth performance in pigs fed diets supplemented with E. faecium DSM 7134 and the blend of OAs and MCFAs. Supplementation with OAs may reduce gut pH (de Lange et al 2010).…”
Section: Discussionsupporting
confidence: 70%
“…In a similar study, with weanling piglets, Mohana Devi and observed that the ATTD of DM and N were increased by supplementation with a combination of MCFAs (caproic acid, caprylic acid, capric acid, and lauric acid) and E. faecium DSM 7134 compared with control diet or diets supplemented with MCFAs or E. faecium DSM 7134 alone. Zhang et al (2016) also demonstrated that a combination of benzoic acid and E. faecium SF68 had positive effect on ATTD of N. In the present study, the increased ATTD of DM and N may be a possible reason for the improvement in growth performance in pigs fed diets supplemented with E. faecium DSM 7134 and the blend of OAs and MCFAs. Supplementation with OAs may reduce gut pH (de Lange et al 2010).…”
Section: Discussionsupporting
confidence: 70%
“…No animal was removed from the study because of disease, which could reflect a good health condition in the environment and high health status, which does not allow us to conclude on any additive effect in relation to diarrhoea incidence. These results agree with previous studies in which additive supplementation, such as organic acids (BOAS et al, 2016;ZHANG et al, 2016), manan-oligosaccharides (CHE et al, 2012), or a combination of these (CORASSA et al, 2012), did not influence faecal scores in weaned piglets.…”
Section: Discussionsupporting
confidence: 83%
“…The low growth performance observed in this phase is directly related to the occurrence of gastrointestinal disorders, mainly diarrhoea caused by pathogenic bacteria (ADEWOLE et al, 2016). Thus, dietary additives such as organic acids (BOAS et al, 2016;DEVI et al, 2016;ZHANG et al, 2016) and mannan-oligosaccharides (FESSELE; LINDHORST, 2013;GIANNENAS et al, 2016;WENNER et al, 2013) have been used to increase growth performance, decrease diarrhoea mortality, and modify the intestinal environment of pigs after weaning.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tan et al (2015) the use of oregano essential oil improved performance of their piglets through reducing oxidative stress. Benzoic acid has the capacity to increase the digestibility of the diet and, consequently, improve the performance of weaned piglets (Zhang et al, 2016). In this way, all these additives have beneficial effects over the performance of piglets; however, the mode of action should be better understood.…”
Section: Introductionmentioning
confidence: 99%